Legal Protection for Creditors Due to Problem Credit with Collateral Rights Guarantee - Arifardhani, Yoyo; Jum Anggriani; Silvia Dantyana (Jurnal Smart Hukum (JSH), 2025)
Legal consequences of the implementation of the Power of Attorney to Charge Mortgage Rights in the implementation of the Sale and Purchase Agreement by a Notary based on the main agreement, namely the Credit Agreement in Banking which is not followed by the making of a Deed of Granting Mortgage Rights and analyzing legal protection for creditors in credit agreements with the execution of mortgage guarantees if the debtor is in default for settlement due to problematic credit. Based on Article 8 of Law No. 10 of 1998 concerning Amendments to Law No. 7 of 1992 concerning Banking in providing credit, banks apply the principle of "5C" which is mainly to see the customer's ability to accept the credit applied for. If the debtor defaults so that problematic credit occurs, then they can file for the execution of the Mortgage Guarantee if the collateral is in the form of land or buildings for the implementation of the SKMHT along with the APHT by a Notary. The purpose of this study was to determine the regulations for debtors who are in default in credit agreements with the imposition of Mortgage Rights and legal protection for creditors in the event that the debtor is in default. By using normative-empirical research methods, data collection techniques in the form of primary data by interviewing informants as informants and secondary data in the form of documents related to the problems studied to obtain conclusions if the debtor defaults in a credit agreement with the imposition of Mortgage Rights, based on the regulations of Law No. 4 of 1996 concerning Mortgage Rights, it states that the imposition is carried out by making a credit agreement first, then the imposition of mortgage rights and registration of the Deed of Granting Mortgage Rights with a predetermined time limit. So that there is legal protection for creditors so that the debtor's debt repayment can be carried out in accordance with the provisions of the Mortgage Law concerning the creditor's right to sell the object of the mortgage right